Further understanding of glioma mechanisms of pathogenesis: implications for therapeutic development. Issue 5 (3rd May 2020) - Ruff, Michael; Kizilbash, Sani; Buckner, Jan
ABSTRACT: Introduction : Recent discoveries in the molecular makeup of gliomas, the relationship of certain molecular drivers, and the patient's response to therapy and overall prognosis have resulted in a paradigm shift and redefined our understanding of glioma and revealed potential vulnerabilities within this recalcitrant and lethal disease. Areas covered : We summarize the current classification of malignant glioma in the context of the historical background, current data-driven treatment strategies, and recent discoveries of the mechanisms of pathogenesis of this disease which recapitulates the developing brain. We describe the relationship to common genetic alterations found in glioma, and possible avenues to exploit these newly revealed mechanisms. Expert opinion : Improved understanding of the molecular underpinnings of this disease has been directly translated into treatment decisions and an improved ability to counsel patients regarding their prognosis. We are beginning to see the first glimmer of a return on the investment in regard to immunotherapy in malignant glioma, with further anticipated successful exploitations of the unique pathophysiology of glioma.